The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1139/b11-076
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of geranium foliage by Clonostachys rosea f. catenulata, a biological control agent of botrytis grey mould

Abstract: The ecological requirements for the colonization of geranium leaves by the biocontrol agent Clonostachys rosea f. catenulata strain J1446 were investigated. Although this biocontrol agent is a soil-inhabiting fungus, treatment of geranium foliage with the agent can reduce grey mould caused by Botrytis cinerea in the greenhouse. To characterize the extent of foliar colonization, a GUS-transformed isolate of C. rosea f. catenulata was applied to foliage of two geranium cultivars, Pelargonium × hortorum and Pelar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Clonostachys rosea could colonize on all the parts of Thrips tabaci and decrease the damage caused by thrips and feeding punctures (Muvea et al 2014). As well, C. rosea f. catenulata could successfully colonize on foliage of geranium cultivars at 20-25°C, and roots of cucumber cultivar at 18-22°C (Chatterton and Punja 2010; Chatterton and Punja 2012).…”
Section: Biological Characteristicsmentioning
confidence: 99%
“…Clonostachys rosea could colonize on all the parts of Thrips tabaci and decrease the damage caused by thrips and feeding punctures (Muvea et al 2014). As well, C. rosea f. catenulata could successfully colonize on foliage of geranium cultivars at 20-25°C, and roots of cucumber cultivar at 18-22°C (Chatterton and Punja 2010; Chatterton and Punja 2012).…”
Section: Biological Characteristicsmentioning
confidence: 99%
“…This result is in accordance with a study of B. subtilis on a strawberry based on next-generation sequencing [ 55 ]. In terms of C. rosea , it was confirmed that C. rosea could successfully colonize the foliage of geraniums and the roots of cucumbers by using a GUS-transformed isolate, demonstrating the endophytic ability of C. rosea in foliar and root tissues [ 14 , 47 ]. In this study, DNA of C. rosea was directly extracted from tomato plants, and the fungal dynamics were analyzed by real-time qPCR to quantify C. rosea DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we applied C. rosea at 10 7 conidia mL −1 concentration for the control of B. cinerea in our pot experiments and halved the concentration of C. rosea to 5 × 10 6 conidia mL −1 when combined with the fungicides. Based on Chatterton and Punja’s research, environmental factors such as temperature and pH were major factors that influenced population levels of C. rosea [ 14 , 47 ]. The optimum temperature for leaf colonization was 20–25 °C, and maximum population densities on the leaves required at least 12 h of continuous leaf wetness [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations